Gerakan Sosial (Wuat Wa’i) pada Masyarakat Desa Gurung Liwut - Haman, Rikhardus; Darmana, I Ketut; ., Aliffiati (Humanis; Vol 25 No 1 (2021), 2021)
One of the traditions that is still preserved today in the village of Gurng Liwut is the wuat wa'i tradition. The procession of the Wuat Wa'i tradition emphasizes the participation of the local community. The preservation of the tradition of wuat wa'i is based on community behavior which upholds the value of solidarity and integrity towards an innovative society in advancing and prospering social life.  The formulation of the problems in this study include (1). How is the function of wa'i in the community of Gurung Liwut Village, Borong District, East Manggarai Regency? (2). What is the existence of the Wuat Wa'i tradition in the people of Gurung Liwut Village? This study aims to determine the function of the Wuat Wa'i tradition and explain the meaning of the Wuat Wa'i tradition for the people of Gurung Liwut Village. This research uses functional theory from Bronislaw Malinowski and Giving from Marcel Mauss. The method used is a qualitative research method. Data collection techniques include observation, interviews, and literature study. The analysis used is descriptive qualitative.  The results of this study reveal that in the tradition of wuat wa'i there is a relationship between moral values, economic improvement, and improvement in formal education. The implementation of the Wuat Wa'i tradition is a social movement that raises funds to finance formal education and increase capital for someone who goes abroad, both at home and abroad. There are various processes in carrying out the tradition of wuat wa'i, namely the deliberation of the event organizers, determining the good day, the completeness of the event material.  The conclusion of this research is that the tradition of wuat  wa'i is a clear proof of the motivation of the local community for the importance of learning through formal education and desires to improve the community's economy through experience gained in the land of thechain .